Cleaning and Disinfection Practices in Digestive Endoscopy in Spain: Results of a National Survey - Brullet, E.; Ramirez-Armengol, J. A.; Campo, R.; null (Endoscopy, 2001)
Disinfection and surveil- lance of it are important for ensuring safety in gastrointestinal endoscopy. The aim of this survey was to assess the current status of disinfection in gastrointestinal endoscopy units in Spain.An anonymous questionnaire on cleaning and disinfection methods was sent to gastrointestinal endoscopy units at 244 public hospitals in Spain. A minimum standard of disinfection (MSD) was defined to evaluate the appropriateness of disinfection practices.A total of 144 centers responded (58 %). All units perform manual washing of endoscopes before disinfection. Automatic washers are available in only 23 % of the centers. Selective cleaning of internal channels is systematically performed in 85 % of the centers. Glutar aldehyde-based disinfectants are the most commonly employed (84 % of units). The time of exposure to the disinfectant is at least 10 min in 97 % of units, but 20 min or more in only 36 % of them. Endoscopic accessories are sterilized in 57 % of centers. The MSD was complied with by 79 % of the units evaluated. Compliance with the MSD was significantly lower in small units (P = 0.0005) performing small numbers of examinations per month. Quality control tests on the efficacy of disinfection methods are conducted at 66 % of the centers. Specialized personnel record disinfection procedures in 85 % of the centers and supervise them in 55 % of the centers. Half of the units have inadequate equipment and facilities.This survey suggests that cleaning and disinfection practices in gastrointestinal endoscopy units in Spain have improved in recent years, and that there is a good compliance with standard guidelines. Most units should improve their equipment and facilities in order to provide better comfort and safety for patients and staff.